2015
DOI: 10.5603/fm.2015.0006
|View full text |Cite
|
Sign up to set email alerts
|

Occlusion of retinal capillaries caused by glial cell proliferation in chronic ocular inflammation

Abstract: The inner blood-retinal barrier is a gliovascular unit in which glial

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 49 publications
0
6
0
1
Order By: Relevance
“…The basement membrane (BM) has a lighter tone and surrounds the pericytes separating them from the endothelium. Macroglia were identified by their abundance of electron-dense endoplasmic reticulum in the cytoplasm(Bianchi et al, 2015;Wakakura & Foulds, 1988). Digital zooming of images was used to identify juxtaposed cell boundaries from two neighbouring cells(File S5: 10.25405/data.ncl.19597255).For the purposes of this study, Müller cells and astrocytes were grouped together as macroglia since in most cases they could not be discriminated from one another in SBF-SEM images.…”
mentioning
confidence: 99%
“…The basement membrane (BM) has a lighter tone and surrounds the pericytes separating them from the endothelium. Macroglia were identified by their abundance of electron-dense endoplasmic reticulum in the cytoplasm(Bianchi et al, 2015;Wakakura & Foulds, 1988). Digital zooming of images was used to identify juxtaposed cell boundaries from two neighbouring cells(File S5: 10.25405/data.ncl.19597255).For the purposes of this study, Müller cells and astrocytes were grouped together as macroglia since in most cases they could not be discriminated from one another in SBF-SEM images.…”
mentioning
confidence: 99%
“…Considering what has been said so far, it clearly emerges that curcumin, the main polyphenolic compound of the food flavoring turmeric, has gained significant interest due to its biological anti-tumoral, antioxidant, immune-modulating, anti-inflammatory, antiparasitic and antiviral properties (61,62). For this reason, it has been extensively studied in different fields of medicine, in general, and particularly, in ophthalmology, where inflammatory cytokines are involved in the development of many ocular diseases, such as conjunctivitis, keratitis, uveitis, glaucoma, age-related macular degeneration and diabetic retinopathy (63)(64)(65)(66)(67)(68).…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that the increased viability of retinal glial cells is one of the important reasons for the pathological changes in glaucoma, and also one of the important signs of retinal degeneration [13]. Glial cells are important retinal cells that regulate neuronal activity and affect neuronal survival in various kinds of injury.…”
Section: Discussionmentioning
confidence: 99%